Evaluating NewSQL Against Legacy Relational Databases and Schema-less Data Stores for Distributed Applications - Verma, Gaurav; Kumar, Amit; Pathak, Gaurav; Singh, Ayush (Indian Journal of Computer Science, 2025)
The present research looks into the phenomenon of NewSQL databases as possible challengers to both RDBMS and NoSQL systems. It studies how NewSQL merges the flexibility and scalability of NoSQL with the strong consistency and transactional capabilities of RDBMS. A comparative analysis is conducted along primary lines such as data model, scalability, consistency, overall performance, transaction support, and real world penetration. The approach taken in this study is both theoretical and case-based, with insights from industry use cases as well as academic literature forming the backbone of the reasoning. The results show that NewSQL has considerably stronger advantages in environments that are distributed and require strong consistency like healthcare and financial services, as well as real-time analytics. However, it does not serve all purposes; mature, structured systems tend to have a traditional RDBMS backbone, while NoSQL is still preferred for schema-less, high-ingestion environments.